NPi-Cluster: a Low Power Energy-Proportional Computing Cluster Architecture - Filho, Sebastião Emidio Alves; Burlamaqui, Aquiles Medeiros Filgueira; Aroca, Rafael Vidal; Gonçalves, Luiz Marcos Garcia (Institute of Electrical and Electronics Engineers, 2017)
This paper presents the NPi-Cluster, an energy proportional computing cluster that automatically powers ON or OFF the number of running machines according to the actual processing demand. A theoretical model is proposed, discussed, and implemented on a cluster composed of Raspberry Pi computer boards designed and built in order to test the proposed system architecture. Experimental results show adequate performance of the proposed platform when compared with other web servers running on traditional server architectures, but with considerably less power consumption. The power consumption of the entire cluster is about 14 W when running at maximum performance. In this situation, the system is able to handle more than 450 simultaneous requests, with about 1000 transactions per second, making it possible to be used as a server capable of handling real web workloads with acceptable quality of service. When the requests demand is reduced to a minimum, the power consumption is dynamically reduced until less than 2 W. Additionally, the proposed cluster architecture also provides high availability by reducing single points of failure on the system
Keywords: Energy efficiency; Scalability; Quality of service; Distributed computing; Low power electronics